2008
DOI: 10.1080/01443610802042688
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Low-molecular weight heparin in patients with recurrent early miscarriages of unknown aetiology

Abstract: The aim of this randomised prospective study was to assess the efficacy of early thromboprophylaxis with low-molecular weight heparin (LMWH) in women with a history of recurrent first trimester spontaneous abortion or miscarriages without identifiable causes vs no treatment. The study comprised of 340 women with unexplained spontaneous recurrent miscarriages. Patients in group A were prescribed LMWH (Enoxaparin sodium 0.2 ml, 20 mg, once daily subcutaneously) from the time of confirmation of fetal viability by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
100
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 25 publications
4
100
1
3
Order By: Relevance
“…Two clinical trials compared congenital abnormalities in RM patients and they reported similar rates between patients that did and did not receive LMWH [20,21]. In our study, congenital abnormalities were more frequent in LMWH-free group (group A).…”
Section: Discussionsupporting
confidence: 62%
“…Two clinical trials compared congenital abnormalities in RM patients and they reported similar rates between patients that did and did not receive LMWH [20,21]. In our study, congenital abnormalities were more frequent in LMWH-free group (group A).…”
Section: Discussionsupporting
confidence: 62%
“…Application of this sequential data to clinical practice could aid the early prediction of pregnancy outcome, and appropriate and timely counseling of patients. Particularly, earlier prediction of pregnancy outcome could provide appropriate reference to health care providers to establish a treatment plan for recurrent pregnancy losses or implantation failures [43][44][45], initiate earlier management of high risk pregnancies, and precise follow-up of abnormal pregnancies. Therefore, early pregnancy biomarkers such as POD 12 hCG-β level and its fold change based on embryonic age could provide a predictive and appropriate reference to both health care providers and patients and assist earlier management and precise follow-up of women with abnormal or high risk pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…by guest www.bloodjournal.org From analyzed about the effect of heparin alone vs no treatment, when excluding studies with a high risk of bias. 16,17 The use of LMWH was supported by some studies in which a basal prothrombotic state outside of pregnancy was measured in women with previous recurrent miscarriage and without known thrombophilia. [24][25][26] In addition, heparin and LMWH have other biological properties that could be critical for implantation and placentation.…”
Section: Discussionmentioning
confidence: 93%
“…[15][16][17][18][19][20][21][22] Only one trial was placebo-controlled (the ALIFE study), a randomized trial among all-comer women (;85% had a negative thrombophilia workup), which resulted in a turning point: the lack of any beneficial effect of aspirin was clearly demonstrated. In addition, the use of openlabel LMWH combined with aspirin in a third intervention arm did not show any improvement in live-birth rates vs oral placebo.…”
Section: Discussionmentioning
confidence: 99%